Ethnicity without groups - Brubaker, Rogers 1956- (Harvard University Press, 2006)
By shifting the analytical focus from identity to identifications, from groups as entities to group-making projects, from shared culture to categorisation, from substance to process, Brubaker shows that ethnicity, race and nation are not things in the world but perspectives of the world.